2021
DOI: 10.3389/fpsyg.2021.667461
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of COVID-19 Pandemic on Physical Health–Psychological Health, Physical Activity, and Overall Well-Being: The Mediating Role of Emotional Regulation

Abstract: Background: Highly infectious respiratory disease COVID-19 emerged in Wuhan, China, and spread worldwide. Different measures have been adopted worldwide to contain the COVID-19, and these measures have various impacts on health-related quality of life (HRQoL). This study aimed to assess the impact of the COVID-19 pandemic (CP) and lockdown policy on physical health (PH)–psychological health (PsH), physical activity (PA), and overall well-being (OW) in the context of HRQoL, exploring the mediating role of emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 65 publications
1
39
0
1
Order By: Relevance
“…Countries such as Iran with delayed vaccination experienced the fth surge of this infection, with cumulative con rmed deaths of 122, 197 people (2). The negative effect of COVID-19 on different aspects of physical health and well-being and mental health (increasing anxiety and depression) have been proven in other studies (3)(4).…”
Section: Introductionmentioning
confidence: 60%
“…Countries such as Iran with delayed vaccination experienced the fth surge of this infection, with cumulative con rmed deaths of 122, 197 people (2). The negative effect of COVID-19 on different aspects of physical health and well-being and mental health (increasing anxiety and depression) have been proven in other studies (3)(4).…”
Section: Introductionmentioning
confidence: 60%
“…A previous study conducted in Iran revealed that age related to cognitive decline, lower levels of functioning in real life, and older adults' QoL [37]. In addition, impairments in older adults with disabilities have previously been associated with reduced social isolation, social interaction, and loneliness [11,38].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on the QoL of people with disabilities in various countries revealed that the QoL of these populations was a significant reduction during the COVID-19 outbreak [10][11][12]. Older adults had a lower QoL score than the other aged groups, which is negatively affected during the social distancing of the crisis [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HRD's emphasis on building capabilities and increasing performance may aid organizations in identifying methods to increase workers' adaptive performance by offering learning and development opportunities and altering corporate culture and practices. More studies on HRD research is required to better understand workers' adaptable performance and to aid businesses in improving their employees' adaptive performance to survive and prosper (Park, & Park, 2019;Dai et al, 2021). However, despite the importance of adaptive performance in performance enhancement, as demonstrated by the "Strategic HR" literature, which consistently found connections between packages of HR practices and various indices of firm performance, the function of organizational HRM practices as predictor variables of adaptive performance remains underexplored (Tabiu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%